'I'm just not that comfortable with technology': student perceptions of and preferences for Web 2.0 technologies in reflective journals. Issue 3 (3rd May 2016) - O'Connell, Timothy S.; Dyment, Janet E.
Abstract : Encouraging reflective practice and developing reflective practitioners is a goal of many disciplines in higher education. A variety of pedagogical techniques have been used to promote critical reflection including portfolios, narratives and reflective journals. Over the past decade, the use of Web 2.0 technologies with students has been increasingly adopted in higher education settings and many educators have integrated these technologies into reflective assignments. These educators assume that students, who are members of the Net Generation, are technologically savvy and have the ability to integrate the use of Web 2.0 technologies into learning. However, while there have been studies examining the outputs of reflective assignments using Web 2.0 technologies such as blogs, e-portfolios and wikis, there has been little research examining whether or not students actually use technology for these types of assignment if given the choice. Therefore, the purpose of this study was to explore if technology was appropriated or rejected by students for a reflective journaling assignment. Results are based on a content analysis of 42 student journaling assignments and interviews with eight students. Findings suggest that (1) students are not as technologically competent as assumed; (2) students chose to use basic/fundamental technologies (e.g. word processing) because they viewed it as the easiest way to complete the reflective journaling assignment; (3) student perceptions of what makes an assignment 'good' influenced their choice to use Web 2.0 technologies; and (4) overarching student perceptions of higher education and learning impacted their appropriation of technology. Implications are discussed and recommendations for both research and practice are made.